EVALUATION OF INDUSTRIAL ENGINEERING INTERNSHIP PROGRAMS BY THE HYBRID FUZZY DEMATEL-VIKOR METHOD - Amorim Santos, Paulo Henrique; Sotsek Ramos, Nicolle Christine (Revista Gestão da Produção Operações e Sistemas, 2024)
Purpose – The internship is an activity that must be carried out in a real work environment by production engineering students as a requirement for obtaining the degree. The internship programs, in turn, are entities that mediate the processes related to intern student’s admission, achievement and evaluation. The aim of this article is to propose a method to evaluate internship programs in production engineering courses. Research Design - Scientific mapping methods and multicriteria decision-making methods were used. Fuzzy DEMATEL was applied to a group of experts to determine criteria weights, by cause-and-effect evaluation. Subsequently, based on a survey with production engineering students from Brazilian universities, Fuzzy VIKOR was used to classify and evaluate internship programs. Findings - Using bibliographic techniques and analysis of social networks, it was possible to identify the main criteria related to internship quality: the student's technical learning; student employability; development of student interpersonal skills; dealings with social issues; the themes developed during the internship; and the internship model and student experience. The method proved to be useful both for comparing different programs, from different universities, as for comparing the evolution of a single program over time. Practical and social implications - The replication of the method should be done in order to improve new students’ experience in a standardized way as well as identifying improvement points in current internship programs. Originality/valor – Besides the unprecedented proposal of using multicriteria decision making to evaluate internship programs, the bibliographic survey brings original issues on the theme as genre equality and discrimination.